Design of Plate Cutting Machine For Cane Cutter (Saccharum Oficinarum) Use Asetilin Gas - M,C, Tri Atmodjo; Tumpal O. R; Sigit D. Puspito (Bandar Lampung University (UBL), 2012)
Till now process in cuting of plate which is thickness more than 3 mm still do manually by hand, without machine. By process of amputation of plate have weakness that is result of plate cutting less natty and require to be grinded, size measure is less accurate and is inefficient of time.Utilize low quality of hence require to be conducted by scheme and making plate clippers use machine, having higher quality which needed semiautomatic plate cutting machine. Plate cutting machine use gas of asetilin semiautomaticly water down process cutting of plate, accurate size measure, quickening cutting process and result neednt be grinded and also in its scheme require fund about Rp. 2.011.000,-.Design method used is reference study and field study. Reference study that is, by studying and taking literatures and considerations related to problem of scheme of goodness in the form of book, magazine of bulletin, and others. While field study that is, checking directly at workshops of welding and do design of plate cutting machine use gas of asetilin semiautomaticly.From result of scheme of machine can cut thick plate 5-15 mm, with unlimited length. Pursuant to amount of used activator, system activator of transmission enchain rol use motor of DC with energy 20,4Watt 24volt 0,85A 22 rpm. Weight of machine 20 kg with long dimension 495mm, wide 330mm, high 400mm. Spacer of horizontal nosel and vertical by using fastener of thread bolt. Functioning Electronic network to arrange speed that, movement for cutting there is 6 backward movement and speed. The Speed of machine is 0,04m / s.